Arranging Small Molecules with Subnanometer Precision on DNA Origami Substrates for the Single‐Molecule Investigation of Protein–Ligand Interactions. Issue 1 (9th September 2020) - Huang, Jingyuan; Suma, Antonio; Cui, Meiying; Grundmeier, Guido; Carnevale, Vincenzo; Zhang, Yixin; Kielar, Charlotte; Keller, Adrian
Abstract : DNA origami nanostructures are versatile substrates for the single‐molecule investigation of biomolecular interactions as they enable the display of molecular species in complex arrangements. Herein, the fundamental limitations of this approach are explored by displaying pairs of small‐molecule ligands of the protein trypsin on DNA origami substrates and adjusting their ligand–ligand spacing with subnanometer precision. Bidentate binding of trypsin to the ligand pairs is investigated by atomic force microscopy (AFM), microscale thermophoresis (MST), and molecular dynamics simulations. Bidentate trypsin binding is strongly affected by the distance of the ligand pairs and the accessibility of the protein's binding pockets. MST cannot resolve the differences in bidentate trypsin binding because of the nonspecific binding of trypsin to the DNA origami substrates, rendering the AFM‐based single‐molecule detection of binding events superior to ensemble measurements. Finally, even monodentate binding to a single ligand may be affected by subnanometer variations in its position, highlighting the importance of local microenvironments that vary even over molecular distances. While this single‐molecule approach can provide viable information on the effects of ligand arrangements on bidentate protein binding, in‐depth investigations into the nature of local microenvironments will be required to exploit its full potential. Abstract : Pairs of small‐molecule ligands of the protein trypsin are displayed on DNA origami with subnanometer precision. Bidentate trypsin binding is strongly affected by subnanometer variations in ligand–ligand spacing. Protein–ligand binding also depends on local microenvironments that appear to vary even over molecular distances and be influenced by other chemical moieties in the vicinity.